Trends in patient satisfaction in Dutch university medical centers: room for improvement for all - Kleefstra, Sophia M (BMC Health Serv Res, 2015)
BACKGROUND: Results of patient satisfaction research provide hospitals areas for quality improvement. Although it may take several years to achieve such improvement, not all hospitals analyze changes in patient satisfaction over time structurally. Consequently, they lack information from patients’ perspective on effectiveness of improvement programs. This study presents a trend analysis of the patient satisfaction scores in the eight university medical centers in the Netherlands. We focus on the trends, effect size and its consequences for improving patient-centered care. METHODS: The Core Questionnaire for the assessment of Patient satisfaction (COPS) was used in four large-scale nationwide comparative studies (2003–2009). Data were analyzed at a national level, and for each academic hospital separately. We analyzed the polynomial contrasts in the four measurements by performing an univariate analysis of variance (ANCOVA). The trend lines are presented graphically, with the means, SD, F-statistics and the standardized effect size including confidence intervals expressed by Cohen’s d. By analyzing the (logit transformed) percentages of very satisfied patients we examined the change scores. RESULTS: The dataset consisted of 58,055 inpatients and 79,498 outpatients. Significant positive trends were found on national level and hospital level, especially in outpatient departments. Improvement was especially seen on the dimensions “information” and “discharge and aftercare”. Not only university medical centers with a lower score at the start, but surprisingly some best practices and university medical centers with a high initial score improved. CONCLUSIONS: We conclude that significant trends in patient satisfaction can be identified on a national and a hospital level, in inpatient and outpatient departments. The observed effect size expressed by Cohen’s d is rather small. Hospitals have found room for improvement, even hospitals with initial high satisfaction scores. We recommend that hospitals monitor their patient satisfaction scores over time and relate these to quality interventions and organizational changes. Furthermore, we recommend to expand the research to subgroups of unsatisfied patients to improve patient-centered care for all patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12913-015-0766-7) contains supplementary material, which is available to authorized users.